Heterorhabditis beicherriana n. sp. (Nematoda: Heterorhabditidae), a new entomopathogenic nematode from the Shunyi district of Beijing, China - Xing-Yue, Li; Qi-Zhi, Liu; Nermuť, Jiří; Půža, Vladimír; Mráček, Zdeněk (Zootaxa, 2012)
A new heterorhabditid nematode was recovered in orchards in the Beijing area. Morphological and molecular dataconfirmed this nematode as a new species, which belongs to the bacteriophora-group with sister taxa Heterorhabditisbacteriophora and H. georgiana. The nematode was named H. beicherriana n. sp. and is characterized by males,hermaphrodites, females and infective juveniles. In males the peloderan bursa is characterized by the formula 1 2 3 3,spicule length 45 (41–51)μm. Male body length is substantially higher than that of H. bacteriophora and H. georgiana(1028μm vs 820 and 838μm, respectively). In hermaphrodites there are six labial and six cephalic papillae; the vulvalpattern is smooth, rounded or slightly elliptical. Tail is conoid with a moderately prominent post-anal swelling slightlylonger than anal body width. In females vulval lips are non-protruding, tail conical without or with a slightly developedpost-anal swelling, about twice as long as anal body width. In infective juveniles, the body is elongate, slender and straightwhen heat-killed, on average 639μm long, which is longer than in H. bacteriophora (558μm) and H. georgiana (598μm),respectively. Heterorhabditis beicherriana n. sp. is further characterized by internal transcribed spacer (ITS) and D2D3rDNA sequences, the most similar species, H. georgiana, being separated by 21 bp across 994 bp of the ITS and 3 across890 bp of the D2D3 region. ITS and D2D3 regions of H. beicherriana evolved five and one autapomorphies, respectively. Phylogenetic analyses placed H. beicherriana n. sp. as a member of the bacteriophora-group.